Intranasal Administration of the Antisecretory Peptide AF-16 Reduces Edema and Improves Cognitive Function Following Diffuse Traumatic Brain Injury in the Rat - Clausen, Fredrik; Hansson, Hans-Arne; Raud, Johan; Marklund, Niklas (Frontiers in Neurology, 2017)
A synthetic peptide with antisecretory activity, antisecretory factor (AF)-16, improves injury-related deficits in water and ion transport and decreases intracranial pressure after experimental cold lesion injury and encephalitis although its role in traumatic brain injury (TBI) is unknown. AF-16 or an inactive reference peptide was administrated intranasally 30 min following midline fluid percussion injury (mFPI; n = 52), a model of diffuse mild-moderate TBI in rats. Sham-injured (n = 14) or naïve (n = 24) animals were used as controls. The rats survived for either 48 h or 15 days post-injury. At 48 h, the animals were tested in the Morris water maze (MWM) for memory function and their brains analyzed for cerebral edema. Here, mFPI-induced brain edema compared to sham or naïve controls that was significantly reduced by AF-16 treatment (p < 0.05) although MWM performance was not altered. In the 15-day survival groups, the MWM learning and memory abilities as well as histological changes were analyzed. AF-16-treated brain-injured animals shortened both MWM latency and swim path in the learning trials (p < 0.05) and improved probe trial performance compared to brain-injured controls treated with the inactive reference peptide. A modest decrease by AF-16 on TBI-induced changes in hippocampal glial acidic fibrillary protein (GFAP) staining (p = 0.11) was observed. AF-16 treatment did not alter any other immunohistochemical analyses (degenerating neurons, beta-amyloid precursor protein (β-APP), and Olig2). In conclusion, intranasal AF-16-attenuated brain edema and enhanced visuospatial learning and memory following diffuse TBI in the rat. Intranasal administration early post-injury of a promising neuroprotective substance offers a novel treatment approach for TBI.